Population Research, Its Relevance and Topicality - Jelonek, Adam (Bulletin of Geography. Socio-economic Series, 2008)
The first part of the paper divides the field of population research into several categories that the author uses in the further discussion. In addition to identifying problems and processes occurring within the distinguished categories, and to assessing the status of demographic situation, population research should take into account practical forecasting. The other part of the paper presents a topical and most needed programme of research applicable to population geography.